Hubungan Rhinitis Alergi Sebagai Faktor Pencetus Angka Kejadian Asma - Pirdaulina Pasaribu, Teresia; Tobing, Jerry; G.U. Simanjuntak, Salomo (Jurnal Kedokteran Methodist, 2021)
Background: Allergic rhinitis are worldwide health problem that affects everyone, this disease affects 10-30% of the population and is thought to be a risk factor for asthma in several epidemiological studies. Asthma and allergic rhinitis are chronic inflammatory diseases, and they often coexist with as many as 80% of asthmatic patients reporting allergic rhinitis and 15-40% patients of allergic rhintis reporting having asthma. Method : This research is a research using literature review method. Conclusion: There is a relations among incidence of asthma and also allergic rhinitis.